Does the Stock Market Boost Firm Innovation? : Evidence from Chinese Firms - He, Hui (IMF Working Papers; Working Paper, 2017)
The paper analyses the effect of the stock market on firm innovation through the lens of initial public offering (IPO) using uniquely matched Chinese firm-level data. We find that IPOs lead to an increase in both the quantity and quality of firm innovation activity. In addition, IPOs expand a firm's scope of innovation beyond its core business. The impact of IPOs on firm innovation varies across financial constraints, corporate governance, and ownership structures. Our results further illustrate that IPOs induce a firm to increase the number of inventors and enable better retention of existing inventors after the IPO. Finally, we show that the enhanced innovation activity resulting from IPOs increases a firm's Tobin's Q in the long run.